2011
DOI: 10.1245/s10434-011-1709-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Prognostic Gene Expression Profiles from Hepatitis B Virus-Positive Hepatocellular Carcinoma and Adjacent Liver Tissue

Abstract: Variation in gene expression during the nontumor stage as well as the tumor stage may affect the prognosis of HCC patients, and integration of the gene expression profiles of HCC and adjacent liver tissue increases discriminatory effectiveness between patient groups, predicting clinical outcomes with enhanced statistical reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
(42 reference statements)
0
14
0
Order By: Relevance
“…Earlier invasion studies using siRNAs were conducted under conditions of decreased proliferation and increased cell death, which potentially contributed to the decrease in the invasion activity of cancer cells (17)(18)(19)(20). Using HCC microarray datasets, we have evaluated several molecular markers differentially expressed in HCC (21)(22)(23). In the present study, we revealed that PRMT5 was overexpressed in HCC and colorectal cancer tissues and its depletion suppressed the invasion of cancer cell lines without affecting the colony survival.…”
Section: Protein Arginine Methyltransferase 5 Is Implicated In the Agmentioning
confidence: 62%
“…Earlier invasion studies using siRNAs were conducted under conditions of decreased proliferation and increased cell death, which potentially contributed to the decrease in the invasion activity of cancer cells (17)(18)(19)(20). Using HCC microarray datasets, we have evaluated several molecular markers differentially expressed in HCC (21)(22)(23). In the present study, we revealed that PRMT5 was overexpressed in HCC and colorectal cancer tissues and its depletion suppressed the invasion of cancer cell lines without affecting the colony survival.…”
Section: Protein Arginine Methyltransferase 5 Is Implicated In the Agmentioning
confidence: 62%
“…Each batch of EHBH-Sh samples was further divided into two subgroups, which are typical low-risk (LRM) and high-risk metastatic (HRM) HCC as defined in previous reports (14,15). Patients in LRM group were defined as: (i) primary HCC without venous metastases, even in endoscopic vision; and (ii) no recurrence within 2 years after liver resection.…”
Section: Selection Modeling and Validation Of Metastasis Signaturementioning
confidence: 99%
“…Recent gene signature studies are summarized in Table 1. [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] Gene signatures developed in those studies were used to separate patients into 2 or more subgroups with different clinical outcomes, phenotypes, and altered signaling pathways. The methods of developing gene signatures fall into two major groups.…”
Section: Gene Signaturesmentioning
confidence: 99%
“…Most of the gene signature studies belong to this group. [50,52,53,55,57,59,[61][62][63][64][65] The second group of gene signatures concerning defined phenotypes or signaling pathways was derived from the data of cell or animal model studies. [49,51,56,58,60] For examples, Lee et al [49] developed a gene signature of stemness from the gene profiling data of rat fetal liver tissue and Kaposi-Novak et al [51] developed a gene signature of Met signaling pathway using the Met deficient mouse model.…”
Section: Gene Signaturesmentioning
confidence: 99%
See 1 more Smart Citation